2019
DOI: 10.1177/1556984519836896
|View full text |Cite
|
Sign up to set email alerts
|

Graft Patency after Robotically Assisted Coronary Artery Bypass Surgery

Abstract: Objective With advances in robotic instrumentation and technology, both robotically assisted minimally invasive direct coronary artery bypass (RMIDCAB) and totally endoscopic coronary artery bypass (TECAB) have been widely used over the past 20 years. Graft patency is the most important outcome in coronary bypass surgery and is associated with long-term prognosis. In this article we reviewed all experts’ studies in the field of robotic assisted coronary artery bypass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…[ 53 55 ] It has been extensively demonstrated that robotic-assisted, endoscopic, multivessel CABG procedures are safe, feasible and reproducible and lead to excellent outcomes. [ 6 , 8 , 56 , 57 ]…”
Section: Techniques Of Minimally Invasive Coronary Artery Bypass Graftingmentioning
confidence: 99%
“…[ 53 55 ] It has been extensively demonstrated that robotic-assisted, endoscopic, multivessel CABG procedures are safe, feasible and reproducible and lead to excellent outcomes. [ 6 , 8 , 56 , 57 ]…”
Section: Techniques Of Minimally Invasive Coronary Artery Bypass Graftingmentioning
confidence: 99%
“…Previous reports have demonstrated that RA-MIDCAB is a safe and efficacious alternative to traditional CABG, providing favorable short-term outcomes and longterm graft patency (16,17). Additional advantages of the technique include reduced need for blood transfusion, shorter hospital stay, and improved quality of life (18).…”
Section: Ra-midcabmentioning
confidence: 99%
“…The conversion rate for TECAB has been trending down since the Göbölös publication 37 with many recent studies now suggesting rates <1%. 54 Reported operative times have also been decreasing with 20 to 30 cases to overcome the learning curve. 37 , 55 Cross-clamp time and CPB time of 67.9 min and 100.4 min, respectively, were reported in a meta-analysis by Leonard.…”
Section: Totally Endoscopic Coronary Artery Bypassmentioning
confidence: 99%